Business development strategy : a case study of SICEDCO Company, Ho Chi Minh City - Nguyen The Phuong; Tang, John C.S.; Dimmitt, Nicholas J.; Sununta Siengthai; Project 300, Vietnam; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
The sixth district construction and economic development Company (SICEDCO) is one of the largest construction companies of Sai Gon General Construction Company, and so it plays an important role by its contribution in economic development in District 6 in particular and in the Ho Chi Minh in general. Although the company has obtained many achievements in its business operation in the resent years, it also faces many difficulties in its development. The problem at present of the company is how to design and develop markets to further development strategy. The construction industry in recent times is seen to be highly competitive and dynamic in Asian countries in general and in Vietnam in particular. With the rapid increase in HCM city's construction demand and the liberalization of the construction market after its entry into WTO, foreign contractors are presented with tremendous opportunities to participate in construction projects in Vietnam. The SICEDCO Company-a construction company in Ho Chi Minh City is one of Vietnamese construction companies are also actively involved in the national construction arena. How the company competes with their internal and external rivals becomes a major concern for all customers of HCM city in the field of construction sector? To remain progressive in such an environment construction companies that the company need to be aggressive in terms of getting business development strategy. This is where the importance of strategies and business development concepts comes into play. This research paper addresses business development strategies that were used by the SICEDCO Company in its business production activity of construction sector. Initially, a framework is established for this study through the presentation of business development strategy theories. Then, through literature review, common business development strategies are identified, which are in turn later used to compare the data collected from the SICEDCO Company. Data are collected via surveys of the departments of the company. Further conclusions are discussed and future recommendations are also presented.
A research study submitted in partial fulfillment of the requirement for the degree of Master of Business Administration in International Business
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2007
Keywords: SICEDCO Company; Construction industry -- Vietnam -- Planning